Efektivitas Autogate Dalam Menunjang Pengendalian Mobilitas Pemegang Izin Tinggal Dan Visa On Arrival (Voa) - Ohei, Kezia; Raffela, Lala; Agfar, Bimo; Hana, Farida; Mohar, Abbyl (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
AutoGATE is an immigration inspection automation system implemented at a number of international airports in Indonesia. This system was developed to improve service efficiency and supervision of residence permit holders and users of Visa on Arrival (VoA) facilities, not all VoA users can use AutoGATE, especially if they do not meet the requirements for electronic passports or do not have biometric records in the immigration system. This study aims to analyze the effectiveness of using AutoGATE in supporting mobility control of VoA users and residence permit holders. This research uses a qualitative approach with a descriptive case study research type. The qualitative approach was chosen because it is suitable for describing and analyzing in depth the effectiveness of the AutoGATE system in controlling the mobility of residence permit holders and users of the Visa on Arrival (VoA) facility, using three main techniques, namely in-depth interviews, participatory observation, and documentation studies, and to maintain data validity and validity, this research applies source triangulation and technique triangulation techniques. Data from various sources were compared and confirmed with each other, while data from interviews, observations, and documentation were analyzed simultaneously to obtain credible conclusions. The results show that AutoGATE contributes significantly to improving the speed of the immigration process as well as the accuracy of monitoring data. However, the system still faces challenges in cross-agency data integration and biometric validation. This study recommends strengthening the information technology infrastructure and training officers to sustainably improve AutoGATE's performance.